Neurodevelopmental Trajectories in Children With Internalizing, Externalizing and Emotion Dysregulation Symptoms - Blok, Elisabet; Geenjaar, Eloy P. T.; Geenjaar, Eloïse A. W.; Calhoun, Vince D.; White, Tonya (Frontiers in Psychiatry, 2022)
Introduction: Childhood and adolescence are crucial periods for brain and behavioral development. However, it is not yet clear how and when deviations from typical brain development are related to broad domains of psychopathology. Methods: Using three waves of neuroimaging data within the population-based Generation R Study sample, spanning a total age range of 6 - 16 years, we applied normative modeling to establish typical development curves for (sub-)cortical volume in 37 brain regions, and cortical thickness in 32 brain regions. Z-scores representing deviations from typical development were extracted and related to internalizing, externalizing and dysregulation profile (DP) symptoms. Results: Normative modeling showed regional differences in developmental trajectories. Psychopathology symptoms were related to negative deviations from typical development in cortical volume in widespread regions of the cortex and subcortex, and to positive deviations from typical development for cortical thickness in the orbitofrontal, frontal pole, pericalcarine and posterior cingulate regions of the cortex. Discussion: Taken together, this study charts developmental curves across the cerebrum for (sub-)cortical volume and cortical thickness. Our findings show that psychopathology symptoms, are associated with widespread differences in brain development, in which those with DP symptoms are most heavily affected.